Random early detection-quadratic linear: an enhanced active queue management algorithm - Vivian Ogochukwu Nwaocha; Adewole Usman Rufai; Tola John Odule; Theophilus Aniemeka Enem; Lukman Adebayo Ogundele; Suleiman Abu Usman; Samuel Oluwatosin Hassan (Bulletin of Electrical Engineering and Informatics, 2022)
This paper identifies the lone linear drop function for computing the dropping probability between certain queue threshold values as a major weakness for the random early detection (RED) algorithm as it leads to large delay and queue instability. To address this concern, we propose an enhanced RED-based algorithm called random early detection-quadratic linear (referred to as “RED-QL”) active queue management (AQM) which leveraged the benefit of a quadratic packet drop function for a light-to moderate traffic load conditions together with a linear packet drop function for a heavy traffic load condition respectively. Results from ns-3 network simulator using different experimental scenarios clearly reveals that the proposed RED-QL algorithm yields a substantial reduction in delay performance and indeed a reduced average queue size than other three representative AQM algorithms. RED-QL is robust, easy to implement and deploy in routers (both in software and hardware) as no more than the packet drop probability profile of the classic RED’s algorithm implementation needs modest alteration.